Selective inner hair cell loss in a neonate harbor seal (Phoca vitulina) - Morell, Maria; Rojas, Laura; Haulena, Martin; Busse, Björn; Siebert, Ursula; Shadwick, Robert E.; Raverty, Stephen A. (Animals, 2022)
Congenital hearing loss is recognized in humans and other terrestrial species. However, there is a lack of information on its prevalence or pathophysiology in pinnipeds. It is important to have baseline knowledge on marine mammal malformations in the inner ear, to differentiate between congenital and acquired abnormalities, which may be caused by infectious pathogens, age, or anthropogenic interactions, such as noise exposure. Ultrastructural evaluation of the cochlea of a neonate harbor seal (Phoca vitulina) by scanning electron microscopy revealed bilateral loss of inner hair cells with intact outer hair cells. The selective inner hair cell loss was more severe in the basal turn, where high-frequency sounds are encoded. The loss of inner hair cells started around 40% away from the apex or tip of the spiral, reaching a maximum loss of 84.6% of hair cells at 80–85% of the length from the apex. Potential etiologies and consequences are discussed. This is believed to be the first case report of selective inner hair cell loss in a marine mammal neonate, likely congenital.